2018
DOI: 10.1038/s41598-018-32860-x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the effector function of CD8+ T cells by gut microbiota-derived metabolite butyrate

Abstract: The gut microbiota produces metabolites such as short-chain fatty acids (SCFAs) that regulate the energy homeostasis and impact on immune cell function of the host. Recently, innovative approaches based on the oral administration of SCFAs have been discussed for therapeutic modification of inflammatory immune responses in autoimmune diseases. So far, most studies have investigated the SCFA-mediated effects on CD4+ T cells and antigen presenting cells. Here we show that butyrate and, to a lesser degree, propion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
169
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(174 citation statements)
references
References 38 publications
4
169
1
Order By: Relevance
“…Among these are increased gut barrier function, liver glucose metabolism, reduction of IBD associated symptoms and promotion of immune tolerance. Contrary to the latter findings, accumulating data shows SCFA to enhance both CD4 (19)(20)(21) and CD8 (22,23) T cell effector function. Several animal and human trials found SCFA to either lack any therapeutic efficacy or to exacerbate inflammation (16,17,(24)(25)(26)(27).…”
mentioning
confidence: 71%
“…Among these are increased gut barrier function, liver glucose metabolism, reduction of IBD associated symptoms and promotion of immune tolerance. Contrary to the latter findings, accumulating data shows SCFA to enhance both CD4 (19)(20)(21) and CD8 (22,23) T cell effector function. Several animal and human trials found SCFA to either lack any therapeutic efficacy or to exacerbate inflammation (16,17,(24)(25)(26)(27).…”
mentioning
confidence: 71%
“…More recently, several studies support the pro-inflammatory effect of SCFAs. Indeed, acetate, propionate, and especially butyrate increase the IFNγ and Granzyme B secretory activity of CD8 T lymphocytes (Balmer et al, 2016;Luu et al, 2018) and reduce IL-17 secretion by Th17 (Luu et al, 2018) via FFAR2&3 and HDACi activity. Butyrate also allows the differentiation of activated CD8 T lymphocytes toward a memory phenotype (Bachem et al, 2019).…”
Section: Gut Microbiome and Immune System Declinementioning
confidence: 99%
“…Their low consumption on the ISS would result in low SCFA production. Butyrate supplementation increases the secretion of IFNγ by CD8 T lymphocytes (Luu et al, 2018). In humans, it is commonly accepted that a healthy and balanced diet, with a regular intake of dietary fiber through fruits and vegetables, allows the prevention of several diseases with immune deficiencies such as cancer (Wang et al, 2012;Aune et al, 2016), and a better immune response against pathogens (Desai et al, 2016).…”
Section: Gut Microbiome and Immune System Declinementioning
confidence: 99%
“…In addition, the reciprocal changes in abundance of Verrucomicrobia and Proteobacteria respectively, was found associated with better ICI response. Although further mechanistic studies are warranted to explain such observations, some speculated that the positive association of Firmicutes could in part due to their critical role in producing short chain fatty acids (SCFA), a metabolite that has regulatory effect on in ammation and T cell differentiation [56][57][58]. This is especially true for the fermentation of ber to SCFA as the necessary enzymatic processes involved, which are largely dependent upon bacteria within the Clostridia class in the Firmicutes phylum [59].…”
Section: Discussionmentioning
confidence: 99%